Predicting suspended sediment load in Peninsular Malaysia using support vector machine and deep learning algorithms - Essam Y.; Huang Y.F.; Birima A.H.; Ahmed A.N.; El-Shafie A. (Nature Research, 2023)
article; artificial neural network; deep learning; Malaysia; particle resuspension; prediction; reliability; river; short term memory; support vector machine